The A to Z of Judaism - Solomon, Norman, 1933-; Solomon, Norman, 1933- (Lanham, Md. : Scarecrow Press, 2009)
This volume provides a reference source for the study of Judaism. Judaism, the religion of the Jewish people, is one of the first recorded monotheistic religions, and as such is one of the oldest religious traditions still practiced today. While its influences can be seen in the religions of both Christianity and Islam, many of its beliefs, traditions, and practices are unknown. It investigates the complex intermingling of religion, devotion, lifestyle, and culture as it is found in diverse Jewish populations around the world and as it has evolved over the course of recent human history. Judaism, like many other cultural institutions, has rarely remained static, instead, continually investigating and questioning itself, metamorphosing in relation to the world. The author provides a chronology, an introductory essay, a bibliography, and numerous cross-referenced dictionary entries on important persons, writings, institutions, concepts, Hebrew words, philosophy, theology, and religious law.
Editor's foreword / Jon Woronoff -- List of tables -- How to find things in the dictionary chronology of the Jewish religion introduction -- The dictionary --Supplementary tables -- Appendix A: The Mitzvot -- Appendix B: Standard prayer texts -- Appendix C: Reform "platforms" -- Appendix D: An orthodox convention -- Appendix E: Christians and Christianity -- Bibliography -- About the author.
Originally published under title as: Historical dictionary of Judaism.
Includes bibliographical references (p. 475-535)
Description based on print version record.
Keywords: Judaism -- Dictionaries; RELIGION / Judaism / General; Electronic books